PENGARUH PROJECT BASED LEARNING TERHADAP KARAKTER TANGGUNG JAWAB SISWA KELAS III SD NEGERI 1 SUNGGUMINASA - Syahira Ainun S; Nur Abidah Idrus; Hotimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the Project Based Learning (PjBL) model on fostering a sense of responsibility among third-grade students at SD Negeri 1 Sungguminasa during Indonesian language lessons. The research was prompted by challenges regarding low student accountability, which potentially impacts their learning outcomes. Using a quasi-experimental approach with a Nonequivalent Control Group Design, this study compared an experimental class utilizing the PjBL model and a control class applying cooperative learning. Data were gathered through pretests and posttests to monitor changes in student character. The findings reveal that the experimental group’s average responsibility score rose from 61.10 to 86.68, which was higher than the control group's average score of 79.94. The Independent Sample t-Test results obtained a significance value of 0.001 (0.001 < 0.05), indicating a statistically significant difference between the two groups. Based on these findings, it can be concluded that the implementation of the PjBL model exerts a significant influence on strengthening students' responsibility character in elementary education.